Machine translation in natural language processing by implementing artificial neural network modelling techniques: an Analysis - Khan, Fazeel Ahmed; Abubakar, Adamu (International Journal on Perceptive and Cognitive Computing, 2020)
Natural Language Processing is emerging with more efficient algorithms to perform detailed analysis and synthesis on different languages and speech translation with techniques from computer science. Machine translation is emerging from Statistical Machine Translation to a more efficient and robust oriented deep learning based Neural Machine Translation. The limitation in Statistical based MT opens a new spectrum of research in NMT to resolve the existing problemsand explore NMT potential in MT research. This paper comprehensively analyses various NMT models proposed in recent years and their contribution in resolving language translation issues. It also discusses on some NMT based open-source toolkits introduced in recent year and the feature implemented in these toolkits. It also analyses the potential of these toolkits to comply with research in language translation particularly in NMT based techniques